IN-VITRO ANTIBACTERIAL EFFICACY OF COMMON SPICES AND THEIR EFFECT ON PERMEABILITY OF MEMBRANE - K. PAVITHRA VANI,; O. BHAGYA LAKSHMI, (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study is to investigate three different spices for antibacterial activity and also to study their effect on membrane permeability of bacteria. The spices selected were Black pepper (Piper nigrum), Cinnamon (Cinnamomum zeylanicum) and Cloves (Syzygium aromaticum) are routinely consumed in our diet. The spice extracts and essential oils were screened for antibacterial activity by Disc Diffusion Method, followed by determination of MBC by double dilution method. Minimum Bactericidal Concentration (MBC) was determined by the Double Dilution Method. Killing Kinetics were studied to know the time course of lethal action of these spices on Escherichia coli and Staphylococcus aureus. Effect of spices on membrane leakage of bacteria was studied by using a UV-spectrophotometer. The results indicate excellent inhibition on the growth of Gram-positive and Gram-negative bacteria. Among the spices tested cloves and cinnamon were found to be more efficient in killing bacteria followed by black pepper. Leakage of cellular constituents from bacterial cells into the extra cellular medium through membrane having absorption at 260nm (Nucleic acids) and 280nm (Proteins) gradually increased after treating the bacteria with the test compound and proved that this may be one of the modes of bactericidal action. From the experimental results it can be concluded that the above three spices are good antibacterial and prospective phytotherapeutic agents.